BRAND ARCHITECTURE RECOMMENDATIONS FOR TINKER GAMES BRAND ALIGNMENT WITH THE PARENT COMPANY (The Indonesian Journal of Business Administration, 2019)
It is known that the video game industry is growing every year and generate $137.9 billion revenue in 2018 with 11% CAGR, and estimated will reach $180.1 billion in 2021. In contrast, Tinker Games, one of Indonesia mobile game developer, face a declining of their revenue. This declining occurred because of their lack of their marketing campaign and low of their brand awareness. Recently, Tinker Games get a good news that is new investors who join the company and build a new entity that will become a parent company. But, that situation is also create a new problem that is the alignment of Tinker Games with the parent company. The analysis using brand audit concept that consist of brand inventory and brand exploratory. In the brand audit summary, the author assumes that there are five root cause in this research. After knowing the root cause, strategy designed for business solution using brand reinforcement strategy. Solution proposed including build more potential marketing campaign, evaluate current marketing campaign, provide customers engagement forum, create new strong unique differentiation, and create new sub-brand alignment and architecture. Proposed solutions will be implemented in the marketing mix, hopefully that it will solve Tinker Games business issues.Keywords:  Mobile Game, Branding Strategy, Brand Awareness, Brand Audit, Brand Architecture.